Willingness of neigbhorhood urchins in Oyo State to engage in farm estate agricultural initiative (2023)
Neighbourhood urchins are generally considered deviant youths who use extortion, exploitation, petty crimes and sometimes violent means to earn income. Unfortunately, they pose huge threats to societal peace. However, engaging them in empowerment programme such as Farm estate agricultural initiative can curb their atrocities and enhance communal peace. This study therefore explored the willingness of neighbourhood urchins to engage in farm estate agricultural initiative for self-empowerment. Using a multi-stage sampling procedure, 113 neighbourhood urchins were sampled and data obtained with the aid of questionnaire and interview scheduled. Data were collected on respondents' socioeconomic characteristics, awareness, perception, preferred interest, willingness and perceived constraints. Data were analysed using descriptive statistics, chi-square, spearman rho and PPMC. Neighbourhood urchins were mostly male (97.3%), had secondary education (47.8%), unemployed (58.4%) with average age of 23 years. Most (62.8%) of the neighbourhood urchins were not aware of the farm estate agricultural initiatives, had unfavourable perception (61.1%), were unwilling to be engaged (67%) and had low preference in farm estate activities (100%). Also, level of education (69%), level of exposure (59.3%), poverty (68.1%) and fear of adapting to new way of life (71.7%) were considered as severe constraints to participating in farm estate agricultural initiative. Age (t=-0.298, p<0.001), household size (r=-0.184, p<0.051), marital status (x2=l5.875, p< 0.000), educational background (x2=10.387, p< 0.016), Awareness level (x2=7.480, p<0.006), poverty (r=-0.307,p<0.001), Lack of parental care (r=-0.462, p<0.000) and Peer pressure (r=0.385, p<0.000), Lack of motivation of any kind (r=-0.305, p<0.001) had significant relationship with respondents willingness to engage in farm estate agricultural initiative for self-empowerment. Neighbourhood urchins are unwilling to engage in farm estate agricultural initiatives for self-empowerment. Motivational incentives, adequate education and awareness can assist them in bringing about favourable perception and attitudinal change towards active participation.